Analysis Of Nitrite (NO2¯) And Nitrate (NO3¯) Levels In Well Water By Viewing Light Spectrophotometer: Analisis Kadar Nitrit (No2¯) Dan Nitrat (No3¯) Pada Air Sumur Secara Spektrofotometer Sinar Tampak - Mukti Wibowo, Yari; Dwi Ratna Sari, Anita (Jurnal Kimia dan Rekayasa, 2025)
Levels of nitrite and nitrate in water when consumed in large quantities can cause diarrhea, seizures, coma and death. When consumed by infants, it causes blue baby syndrome. The purpose of this study was to determine the levels of nitrite and nitrate contained in the borehole water and to determine whether the levels of nitrite and nitrate in the borehole water met the quality standards of environmental health requirements for sanitation hygiene purposes according to the Regulation of the Minister of Health of the Republic of Indonesia No. 32 of 2017. Determination of nitrite and nitrate levels in well water samples taken from the water laboratory of the Energy and Mineral Resources Office of the Solo Region, the sample came from the Mangkubumen Village, Banjarsari District, Surakarta City using a visible spectrophotometer HACH type 2800 with a nitrite wavelength of 507 nm and nitrate at 420 nm. Based on the results of the study, it was known that the nitrite levels in 3 samples of drilled well water were obtained, namely bore well A 0.012 mg/l; well B 0.005 mg/l; well C 0.003 mg/l and nitrate levels in 3 well water samples, namely well A 0.900 mg/l; well B 0.800 mg/l, well C 0.700 mg/l. The results obtained from the levels of nitrite and nitrate in 3 drilled well water samples met the quality standard of the Minister of Health of the Republic of Indonesia No. 32 of 2017 concerning water requirements for the use of sanitary hygiene, where the nitrite level in water is 1 mg/l and the nitrate level in water is 10 mg/l. AbstrakKadar nitrit dan nitrat dalam air apabila dikonsumsi dalam jumlah besar dapat menyebabkan diare, kejang, koma dan meninggal. Apabila dikonsumsi oleh bayi menyebabkan blue baby syndrome. Tujuan penelitian ini untuk mengetahui berapakah kadar nitrit dan nitrat yang terdapat di dalam air sumur bor dan untuk mengetahui apakah kadar nitrit dan nitrat dalam air sumur bor memenuhi baku mutu persyaratan kesehatan lingkungan untuk keperluan higiene sanitasi menurut Peraturan Menteri Kesehatan RI No.32 Tahun 2017. Penentuan kadar nitrit dan nitrat pada sampel air sumur yang diambil dari laboratorium air Cabang Dinas Energi dan Sumber Daya Mineral Wilayah Solo, sampel tersebut berasal dari daerah Kelurahan Mangkubumen, Kecamatan Banjarsari, Kota Surakarta menggunakan spektrofotometer visibel HACH tipe 2800 dengan panjang gelombang nitrit yaitu 507 nm dan nitrat yaitu 420 nm. Berdasarkan hasil penelitian, diketahui kadar nitrit pada 3 sampel air sumur bor diperoleh hasil yaitu sumur bor A 0,012 mg/l; sumur B 0,005 mg/l; sumur C 0,003 mg/l dan kadar nitrat pada 3 sampel air sumur bor yaitu sumur A 0,900 mg/l; sumur B 0,800 mg/l, sumur C 0,700 mg/l. Hasil yang diperoleh dari kadar nitrit dan nitrat pada 3 sampel air sumur bor memenuhi baku mutu Permenkes RI No. 32 Tahun 2017 tentang persyaratan air untuk kegunaan higiene sanitasi, dimana kadar nitrit dalam air sebesar 1 mg/l dan kadar nitrat dalam air sebesar 10 mg/l.